Political Movements and Forgotten Women of Telangana. Issue 2 (December 2020) - Pathak, Keyoor; Subudhi, Chittaranjan
Telangana became a separate state in 2014 with a lot of sacrifices from women The article provides a brief histography and revolves around those women of Telangana, who actively participated in different political and social movements of Telangana or India as a whole.